Low-Grade Appendiceal Mucinous Neoplasm (LAMN) Primarily Diagnosed as an Ovarian Mucinous Tumor - Konstantinos Perivoliotis; Gregory Christodoulidis; Athina A. Samara; Ioanna-Konstantina Sgantzou; Theodoros Floros; Georgios Volakakis; Foteini Karasavvidou; Konstantinos Tepetes (Case Reports in Surgery)
Background. Low-grade appendiceal mucinous neoplasms (LAMN) are detected in 0.7 to 1.7% of all appendicectomies. The diagnosis can be challenging, particularly in female patients where the differential diagnosis of primary appendiceal and ovarian mucinous neoplasms is unclear. Case Presentation. A 71-year-old female was referred to our tertiary hospital with the working diagnosis of a right ovarian cystic tumor. The lesion was identified through a transvaginal ultrasound performed for vague lower abdominal pain symptoms. CT scan confirmed these findings. Intraoperatively, an appendiceal mucocele was identified and a right hemicolectomy was performed. The histopathology examination revealed a LAMN. Six months later, the patient remains disease-free. A close biannual oncological follow-up has been suggested. Conclusion. This case underlines the difficulty in determining the origin of mucinous neoplasms of the right pelvic area. Mucocele of the appendix should be considered in the differential diagnosis of a mass in the right iliac fossa.